Foreign Aid and Economic Growth: A study of the SADC - Adam, Ashraf (2017)
The aim of this paper is to observe the effectiveness of official development assistance (ODA) on economic growth in 15 African nations that form the Southern African Development Community (SADC). The model developed identifies the main determinants of economic growth using panel data for the period 1990 – 2014. The time frame was split in to two, to observe the relationship over the long run and short run period. The long run included the entire period where as the short run covered 2005 – 2014. The endogenous growth model was used to account for the endogeneity and the General Method of Moments (GMM) estimator was the preferred estimation technique. The results of the study show that foreign aid has a positive effect on GDP per capita in the SADC region. The results over the short run are more robust as they are statistically significant. Growth occurred over the period regardless of the policy and quality of institutions. Additionally,trade openness is vital in facilitating growth.